2015
DOI: 10.1002/etc.2914
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics: addressing ecological risk through lessons learned

Abstract: Plastic litter is an environmental problem of great concern. Despite the magnitude of the plastic pollution in our water bodies, only limited scientific understanding is available about the risk to the environment, particularly for microplastics. The apparent magnitude of the problem calls for quickly developing sound scientific guidance on the ecological risks of microplastics. The authors suggest that future research into microplastics risks should be guided by lessons learned from the more advanced and bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(141 citation statements)
references
References 34 publications
(88 reference statements)
2
125
0
4
Order By: Relevance
“…It is possible that a combination of microscopic particles, leached additives, and other degradation products may cause subtle effects towards aquatic and terrestrial organisms that are difficult to identify in current testing methodologies. The formation of plastic particles in the submicron and nanometer size range during degradation is highly likely [8,40,66,102,103]. Engineered nanoparticles (ENPs) are able to cross cell membranes and become internalised, and the uptake of ENPs is size dependent with uptake occurring by endocytosis or phagocytosis [104].…”
Section: Biological Effects Of Sub-micrometer Plasticsmentioning
confidence: 99%
“…It is possible that a combination of microscopic particles, leached additives, and other degradation products may cause subtle effects towards aquatic and terrestrial organisms that are difficult to identify in current testing methodologies. The formation of plastic particles in the submicron and nanometer size range during degradation is highly likely [8,40,66,102,103]. Engineered nanoparticles (ENPs) are able to cross cell membranes and become internalised, and the uptake of ENPs is size dependent with uptake occurring by endocytosis or phagocytosis [104].…”
Section: Biological Effects Of Sub-micrometer Plasticsmentioning
confidence: 99%
“…Conclusive evidence for the transfer of associated hazardous compounds from plastics to organisms is lacking, but several studies have suggested correlations between plastics ingestion and compromised physiological function (e.g. Teuten et al, 2009;Wright et al, 2013;Syberg et al, 2015). An additional threat of microplastics is their role as colonization surface habitats for bacteria or other organisms, which may lead to the invasive transport of microbial communities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…After the ingestion, the ingestion processes, dominated shifts in pH, temperature and redox conditions, microplastic particles can potentially release the adsorbed environmental pollutants therefore enhancing both their bioavailability and biological adverse effects to biota. This route of exposure for aquatic organisms, the so called "Trojan horse" effect, remains under-investigated with limited data concerning such phenomena (Syberg et al, 2015;Paul-Pont et al, 2016;Gaspar, 2017).…”
Section: Introductionmentioning
confidence: 99%